Assessment of mustard vesicant lung injury and anti‐TNF‐α efficacy in rodents using live‐animal imaging. Issue 1 (9th November 2020) - Murray, Alexa; Gow, Andrew J.; Venosa, Alessandro; Andres, Jaclynn; Malaviya, Rama; Adler, Derek; Yurkow, Edward; Laskin, Jeffrey D.; Laskin, Debra L.
Abstract: Nitrogen mustard (NM) causes acute lung injury, which progresses to fibrosis. This is associated with a macrophage‐dominant inflammatory response and the production of proinflammatory/profibrotic mediators, including tumor necrosis factor alpha (TNF‐α). Herein, we refined magnetic resonance imaging (MRI) and computed tomography (CT) imaging methodologies to track the progression of NM‐induced lung injury in rodents and assess the efficacy of anti‐TNF‐α antibody in mitigating toxicity. Anti‐TNF‐α antibody was administered to rats (15 mg/kg, every 8 days, intravenously) beginning 30 min after treatment with phosphate‐buffered saline control or NM (0.125 mg/kg, intratracheally). Animals were imaged by MRI and CT prior to exposure and 1–28 days postexposure. Using MRI, we characterized acute lung injury and fibrosis by quantifying high‐signal lung volume, which represents edema, inflammation, and tissue consolidation; these pathologies were found to persist for 28 days following NM exposure. CT scans were used to assess structural components of the lung and to register changes in tissue radiodensities. CT scans showed that in control animals, total lung volume increased with time. Treatment of rats with NM caused loss of lung volume; anti‐TNF‐α antibody mitigated this decrease. These studies demonstrate that MRI and CT can be used to monitor lung disease and the impact of therapeutic intervention. Abstract : In the present studies, we used MRI and CT imaging technology to follow the progression of lung injury induced by nitrogen mustard in live animals. By refining analytical methodology, pathologic changes were quantified, and the impact of anti‐TNF‐α antibody assessed. Our results demonstrate that noninvasive MRI and CT imaging methodologies provide a more robust assessment of disease progression and resolution from repeated measurements in the same animals.